Analisis Pengaruh Ethical Climate Terhadap Turnover Intention (Studi Pada Cv Andi Offset) - , Wirawan Setiadi, Mahfud Sholihin, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to examine the effect of ethical climate on turnover intention through intermediate variables of role stress and job satisfaction. The study was conducted through a questionnaire using a Likert Scale 1-5 on CV Andi Offset employee respondents in Yogyakarta with a minimum working period of 6 months. Data that can be analyzed were from 120 questionnaires pieces. The variables used in this study consist of independent variables (ethical climate), the dependent variable (turnover intention) and mediating variable (role stress {role conflict and role ambiguity} and job satisfaction). Data analysis was performed using Structural Equation Modeling (SEM) with an alternative method of Partial Least Square (PLS). The evaluation study included evaluation model of the outer model or measurement model and the evaluation of inner models or structural models. The results showed that ethical climate has a significant effect on role ambiguity and job satisfaction but no significant effect on role conflict